2011
DOI: 10.1159/000330797
|View full text |Cite
|
Sign up to set email alerts
|

mRNA Expression of Bone Morphogenetic Proteins and Their Receptors in Human Renal Cell Carcinoma

Abstract: Introduction: Bone morphogenetic proteins (BMPs) have been studied in several cancers, but only limited information is available about renal cell carcinomas (RCCs). We determined the expression of mRNA of several BMP ligands and BMP receptors (BMPRs) in healthy kidney tissue and RCCs, and data were compared to clinicopathological parameters. Material and Methods: Sixty-four samples of RCCs and healthy renal tissues were prospectively examined. The expression of BMP2, BMP4, BMP6, BMP7, BMPRIA, BMPRIB and BMPRII… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 49 publications
0
8
0
Order By: Relevance
“…This might be explained by the focus on all RCC of the previous study, while our study had specific focus on clear cell subtypes. Markic et al [23] had shown that all BMPs (BMP2, BMP4, BMP6, BMP7) and their receptors (BMPRIA, BMPRIB, and BMPRII) mRNA have stronger expression levels in RCC, especially BMP2 is elevated strongly in kidney cancer. Lee et al reported that BMP6 activated interleukin-10-mediated M2 polarization of tumor-associated macrophages to promote RCC growing.…”
Section: Discussionmentioning
confidence: 99%
“…This might be explained by the focus on all RCC of the previous study, while our study had specific focus on clear cell subtypes. Markic et al [23] had shown that all BMPs (BMP2, BMP4, BMP6, BMP7) and their receptors (BMPRIA, BMPRIB, and BMPRII) mRNA have stronger expression levels in RCC, especially BMP2 is elevated strongly in kidney cancer. Lee et al reported that BMP6 activated interleukin-10-mediated M2 polarization of tumor-associated macrophages to promote RCC growing.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Wang et al [ 18 ] demonstrated that BMP-2 inhibits RCC growth by causing cell cycle arrest in the G1 phase. On the other hand, Markić et al [ 19 ] showed that expression levels of BMP-2 were strongly elevated with increased TNM stage in clinical RCC. However, the biological effects of BMP-2 on RCC development and progression remain to be fully elucidated, because only limited information is available for BMP-2 in human RCC.…”
Section: Introductionmentioning
confidence: 99%
“…Then, a personalized, predictive nomogram with a risk score was developed, which served as a predictive indicator; the signature encompassed a total of 14 IRGs. Among these, SAA1, TNFSF14, FGF21, IFNG, BMP7, and IL11 are biomarkers for predicting RCC outcomes (67)(68)(69)(70)(71)(72). For example, as a member of the serum amyloid A family of apolipoproteins, SAA1 can increase the invasive capacity of tumor cells in RCC by inducing MMP-9 expression (73), which make it serve as a biomarker for the diagnosis and prognosis of advanced and metastatic renal cell carcinoma.…”
Section: Discussionmentioning
confidence: 99%